Bimbingan Belajar Mengatasi Hambatan Belajar Sebagai Upaya Mengoptimalkan Prestasi Belajar Anak Usia Sekolah - TS, Malikatun Khasanatil Marwah; Sa’adah, Nurus (Innovative: Journal Of Social Science Research, 2024)
Individual processes that can change students' attitudes and ways of learning so as to form positive habits, even into the development of optimally obtained knowledge which is tutoring. This study provides a basic question of how a BK teacher provides tutoring to solve academic problems. The type of research used in this study is literature research. The criteria of this study are students who are identified as school-age children, the criteria are based on the results of research on the psychological development of high school children who often change their inner state. The results of this study tutoring combines student learning problems by developing themselves to be able to increase learning achievement, and students getting used to doing positive habits can increase success in learning. Keywords: tutoring; Student Learning Problems